Pengujian Black Box pada Aplikasi Presensi Karyawan dengan Teknik Equivalence Partitioning - Satria Putra Laksmana; Diva Ikbar Rauf; MUHAMAD BURHANUDIN; Damar Wicaksono; Aries Saifudin (CV. Multi Kreasi Media, 2022)
Justification for meeting the objectives and specifications expected from making the application determined and validated through a test. The testing process is a process that needs more attention, errors in the testing process have an impact on the application being tested, for example a bug in the application login process or a mismatch between information in the application database and real information. This can be a bottleneck when the application is being used by the user. In addition, it can also cause employee losses due to the discrepancy between wages and working days. In the end, a higher test validation accuracy is needed. Applications that are designed must go through the testing phase to get high-quality software. The test that we use in this study is the Black Box test using the Equivalence Partitioning method. This test is the process of testing certain features or functions of the software being tested. The simple purpose of this test is to verify the functionality of the application as well as the functionality of the login process. This method of testing is used because it is believed that it is in accordance with the Employee Presence application being tested. In this test, we tested the login function, scanned the QR, and printed out the Employee Attendance report. As a result, from a total of 9 times of testing, all of them operate well according to the design expectations so that it can be concluded that this application has complied with the requirements.